Prinsip-Prinsip Manajemen Bisnis Keluarga (Family Business) Dikaitkan Dengan Kedudukan Mandiri Perseroan Terbatas (PT) - Augustinus Simanjuntak (Jurnal Manajemen dan Wirausaha, 2010)
Family members as owner or majority stakeholders in a company often making deep intervension to their company by ignore principles of business management. Therefore, boards of directors, after pressure by owner, often making decisions which is damaging others. One of that company form is limited corporation (ltd. corp) so that its management must be done professionally. But, professionality of limited corporate management often hampered by strong influence or negative intervension (unhonesty) from owner. Whereas, according to Law number 40 of 2007 regarding to Limited Corporation, corporation is autonomous or independent company in business act and making decision. Therefore, the liability of a limited corporation just limited on its own property. It means that when there is an large unpayable debt of company, owner and board of directors are not involved to get liability of debt even to his individual properties. The autonomy of this limited corporation will give consequencies to its management system that its management must be submit to the law.